Effect of prostaglandin analogs on matrix metalloproteinases and tissue inhibitor of metalloproteinases in eyelid muscle specimens - Karli S (Dove Medical Press, 2018)
Sapir Karli, Juan Alfredo Ayala-Haedo, William J Feuer, Maria Fernandez, Sander Dubovy, Sara T Wester Bascom Palmer Eye Institute, Miami, FL, USA Purpose: To characterize the effect of prostaglandin analogs (PAs) on tissue specific expression of matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) in levator aponeurosis resections (LAR) and conjunctiva-Muller muscle resections (CMMR).Methods: Specimens from LAR and CMMR of PA users and non-users were analyzed for tissue specific expression of MMP-3, MMP-7, MMP-9 and TIMP-2 using immunohistochemistry. PA use, marginal reflex distances, levator function and palpebral fissure were documented through chart review. The associations between MMP expression, PA exposure time and ocular characteristics were evaluated with a two-factor analysis of variance and multiple correlation analysis.Results: We observed a tissue specific pattern of expression of MMPs and TIMP-2 in relation to PA exposure between CMMR and LAR specimens. There was increased MMP-7 and TIMP-2 expression in muscle compared to collagen and adipose tissue (P≤0.005), as well as a statistically significant difference in the relationship of MMP-3, MMP-9 and TIMP-2 levels to PA exposure in the two types of muscles (all P≤0.011). Adipose tissue had a PA-dependent reduced expression of MMP-3 (P<0.022), which was seen in both LAR and CMMR. Decreased expression of MMP-3 in collagen correlated with increased dermatochalasis (P<0.045) and steatoblepharon (P<0.018).Conclusion: PA exposure may affect MMP and TIMP expression in a tissue specific manner, and decreased expression of certain MMPs in collagen correlates to increased clinical measures of prostaglandin associated periorbitopathy (PAP). Further studies with larger samples are needed to ascertain if the changes associated with PAP are due to MMP/TIMP changes or to structural changes. Keywords: MMP, matrix metalloproteinase, prostaglandin associated periorbitopathy, PAP, prostaglandin analog, periorbitopathy